Analisis Penerapan Tarif Efektif Rata-Rata (TER) Terhadap Perhitungan Pajak Penghasilan Pasal 21 Pegawai Pemerintah Pada Dinas Pertanian Kab. Agam - Dewi Susanti; Ratnawati Raflis (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
Article 21 Income Tax is one of the largest sources of state revenue and directly relates to employees. At the end of 2023, the government introduced a new regulation through Government Regulation No. 58 of 2023 and Minister of Finance Regulation No. 168 of 2023 by implementing the Average Effective Rate (AER), effective January 1, 2024. This study aims to analyze the implementation of AER in calculating Article 21 Income Tax and compare it with the previous method for ASN employees at the Department of Agriculture of Agam Regency. This research uses a qualitative method with a comparative approach. The results indicate that AER simplifies tax calculations and provides a more proportional tax burden compared to the previous system.